MICROBIOLOGICAL AND ANTIBACTERIAL CHARACTERISTICS OF UROSEPTIC COLLECTION FROM MEDICINAL PLANT - Zamira R. Fayzullayeva; Zuhra A. Nuruzova; Gulshoda A. Xalimjonova; Ruskhsora O.Boymamadova; Raykhona K. Alisherova (Central Asian Journal of Medicine, 2024)
The purpose of this work was to determine the anti-inflammatory and antibacterial activity of “phytourosept” in an experiment and to evaluate its pharmacotherapeutic effectiveness in the complex treatment of patients with acute pyelonephritis. Material and methods: A new herbal remedy in the form of a dry extract from the herb Polygonum aviculare L., shoots of Arctostaphylos uva ursi L., flowers of Calendula officinalis L., leaf of Urtica dioica L., leaf of Vaccinium vitis idaea L. has pronounced anti-inflammatory and antibacterial properties that determine its pharmacotherapeutic effectiveness in the complex treatment of patients with acute pyelonephritis. Conclusion: The data obtained on the pronounced antibacterial and anti-inflammatory activity of “phytourosept” argue for the feasibility of its use in clinical practice as an effective safe agent intended for the treatment and prevention of infectious diseases of the urinary tract.